JURIDICAL STUDY OF CIRCUMS BY NURSES IN INDEPENDENT NURSING PRACTICES - Junaedi Junaedi (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
One cultural heritage of the Indonesian nation is the traditional Etu boxing tradition. Apart from being loaded with various skills and skills for self-defense, studying the Etu custom is also to test the virility and courage of youths in Nagekeo Regency, which is rich with the traditions surrounding it. Sports reviewing Etu customs are rich in socio-cultural values and philosophical meanings. This study aims to determine: 1) The noble values contained in Etu sports, 2) Describe the formation of Community Character in Etu sports, and 3). Describing Sports Activities For Schools. in the Nagekeo district of East Nusa Tenggara, and saw the process of inheriting the traditional Etu sport of boxing from generation to generation. This study uses a data approach obtained using Miles Matthew's analysis. B and Huberman Michael, which consists of three stages, namely data reduction and data presentation, and ends with concluding. The results of the study show that the study of Etu adat is not just a sport. Sport observing the Etu custom is a means to gain movement experience, which is helpful for the growth and development of physical and fitness, mental and courage, in addition to uniting and familiarizing one another, but values and meaning in society. The process of inheriting the traditional Etu boxing tradition has also been going well until now